2019
DOI: 10.1186/s13104-019-4579-3
|View full text |Cite
|
Sign up to set email alerts
|

The pulsed ultrasound strategy effectively decreases the S. aureus population of chronic rhinosinusitis patients

Abstract: Objective Staphylococcus aureus with the ability of biofilm formation and the drug resistance acquisition is one of the most frequently isolated pathogens from chronic rhinosinusitis patients. Ultrasound as an alternative therapy is effectively able to kill the bacteria by cavitation in or on the bacterial cells and peroxide generation and hence improving antibiotic treatment efficacy. Results Staphylococcus aureus was detected in 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…In many studies were enrolled patients whose previous treatments (medical treatment or surgery) had not been effective in relieving symptoms. 5,15,16,19,20 The studies had assumed pretest-posttest design 5,15,17 and single- 15,17,20,21 or double-blinded 19,22 randomized…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many studies were enrolled patients whose previous treatments (medical treatment or surgery) had not been effective in relieving symptoms. 5,15,16,19,20 The studies had assumed pretest-posttest design 5,15,17 and single- 15,17,20,21 or double-blinded 19,22 randomized…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias graph: review authors' judgements about each risk of bias item presented as percentages across all included studies controlled trial. The modalities of therapeutic ultrasound investigated were pulsed 15,16,19,20,22,24 and continuous, 17,[21][22][23] and the studies evaluated the ultrasound effects immediately after one session (shortterm effects) 18 or after a few sessions (long-term effects) 5,[15][16][17]19,21,22,25 of treatment. The main outcomes evaluated, and the results of the studies included in this review are summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the application of new methods of biofilm destruction may reduce the extent and chronicity of the disease. Amongst the promising methods that could be implemented in AD are, for example, the pulse ultrasound [27, 28] and the application of antimicrobial peptides [29, 30] to the anterior nares as long-time prevention of S. aureus dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Hauck et al reported both continuous or pulsed ultrasound could improve endothelial function in a randomized clinical trial of 30 patients (109).It appears that LIPUS is also efficient at treating bacterial infection. For example, Feizabadi et al reported that LIPUS decreased the population of Staphylococcus aureus in chronic rhinosinusitis patients(110). Karosi et al exposed nasal polyps removed from a patient with chronic rhinosinusitis to low-intensity continuous ultrasound(114) and found…”
mentioning
confidence: 99%